In vitro and in vivo activity of Manuka honey against NDM-1-producing Klebsiella pneumoniae ST11. (January 2018) - Qamar, Muhammad Usman; Saleem, Sidrah; Toleman, Mark Alexander; Saqalein, Muhammad; Waseem, Muhammad; Nisar, Muhammad Atif; Khurshid, Mohsin; Taj, Zeeshan; Jahan, Shah
Aim: To determine the therapeutic potential of Manuka honey against New Delhi metallo-β-lactamase-1-producing Klebsiella pneumoniae ST11 in vitro and in vivo .Materials & methods: Carbapenamases and metallo-β-lactamases-producing K. pneumoniae ST11 isolated from blood culture was confirmed by VITEK-2 ® system, matrix-assisted laser desorption ionization–time of flight and multilocus sequence typing, followed by determination of minimum inhibitory concentration (μg/ml) using VITEK-2 system. Genetic analysis of bla NDM-1 was done by PCR, pulsed-field gel electrophoresis and DNA hybridization. In vitro and in vivo efficacy of Manuka honey was performed by microbroth dilution assay and BALB/c mice model respectively.Results: K. pneumoniae ST11 displayed resistance to commonly used antibiotics. bla NDM-1 was located on 150 and 270kb plasmids. Minimum inhibitory concentration and minimum bactericidal concentration of Manuka honey was 30% ( v/v ) and substantial reduction of bacterial mean log value (>1 log) was observed in mice. Histological analysis of mice liver and kidneys demonstrated mild to moderate inflammation.Conclusion: Manuka honey can be used as an alternate therapeutic approach for management of New Delhi metallo-β-lactamase-producing pathogens.